Pengaruh Digital Marketing terhadap Brand Awareness dalam Penggunaan E-commerce - Pramayanti, Dian Ikha (Universitas Ngudi Waluyo, 2024)
The use of E-commerce as a marketing channel has rapidly expanded, prompting organizations to better understand the influence of Digital marketing on Brand awareness. This research adopts a qualitative approach to explore consumers' perceptions and experiences regarding digital marketing strategies implemented by E-commerce companies. The research findings indicate that Digital marketing significantly contributes to the enhancement of Brand awareness in the context of E-commerce. Strategies such as social media, digital advertising campaigns, and search engine optimization have a positive impact on brand awareness among consumers. Additionally, consumer interactions with digital content, such as product reviews and testimonials, play a crucial role in shaping brand perceptions. This study provides in-depth insights into how Digital marketing can be an effective tool for boosting Brand awareness in the era of E-commerce. Abstrak Penggunaan E-commerce sebagai saluran pemasaran telah berkembang pesat, mendorong organisasi untuk lebih memahami pengaruh Digital marketing terhadap Brand awareness. Penelitian ini mengadopsi pendekatan kualitatif untuk menggali persepsi dan pengalaman konsumen terhadap strategi pemasaran digital yang diterapkan oleh perusahaan E-commerce. Hasil penelitian menunjukkan bahwa Digital marketing berkontribusi signifikan terhadap peningkatan Brand awareness dalam konteks E-commerce. Strategi seperti media sosial, kampanye iklan digital, dan optimasi mesin pencari memberikan dampak positif terhadap kesadaran merek di kalangan konsumen. Selain itu, interaksi konsumen dengan konten digital, seperti ulasan produk dan testimoni, memiliki peran penting dalam membentuk persepsi merek. Penelitian ini memberikan wawasan mendalam tentang bagaimana Digital marketing dapat menjadi alat yang efektif untuk meningkatkan Brand awareness di era E-commerce.